2022
DOI: 10.1161/jaha.121.023694
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype‐Directed Management of Hypertension in Pregnancy

Abstract: Hypertensive disorders of pregnancy are among the most serious conditions that pregnancy care providers face; however, little attention has been paid to the concept of tailoring clinical care to reduce associated adverse maternal and perinatal outcomes based on the underlying disease pathogenesis. This narrative review discusses the integration of phenotype‐based clinical strategies in the management of high‐risk pregnant patients that are currently not common clinical practice: real‐time placental growth fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 80 publications
(118 reference statements)
0
1
0
1
Order By: Relevance
“…Several studies have demonstrated changes in the concentration of placental biomarkers relating to changes in placental function and fetal health, reflecting the assessment of early placental development, which is driven by a combination of genetic and environmental factors. 14 Maternal blood biomarkers were originally developed for detecting aneuploidy and over the past decade have been proposed to help with risk stratification for PE, [15][16][17][18] but they could also be useful for early detection of FGR since both FGR and PE share commonalities including the underlying placental dysfunction. 19,20 As such we explore the use of placental biomarkers for the prediction and prevention of FGR and developing agents of treatment in this population and highlight the potential specific biomarkers for fetal origins of adult disease.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated changes in the concentration of placental biomarkers relating to changes in placental function and fetal health, reflecting the assessment of early placental development, which is driven by a combination of genetic and environmental factors. 14 Maternal blood biomarkers were originally developed for detecting aneuploidy and over the past decade have been proposed to help with risk stratification for PE, [15][16][17][18] but they could also be useful for early detection of FGR since both FGR and PE share commonalities including the underlying placental dysfunction. 19,20 As such we explore the use of placental biomarkers for the prediction and prevention of FGR and developing agents of treatment in this population and highlight the potential specific biomarkers for fetal origins of adult disease.…”
Section: Introductionmentioning
confidence: 99%
“…Нарушение инвазии вневорсинчатого цитотрофобласта и неполноценное ремоделирование спиральных маточных артерий приводит к патоморфологическим изменениям маточно-плацентарного кровотока и ранней манифестации ПЭ, в основном, тяжелого течения [6]. Развитие поздней ПЭ обусловлено, преимущественно, наличием особенностей функционирования сердечно-сосудистой системы и гемодинамики матери и сопровождается умеренным течением [7]. Тяжелое течение ПЭ сопряжено с более высокими рисками развития неблагоприятных последствий.…”
unclassified